Radiographic characteristics in congenital scoliosis associated with split cord malformation: a retrospective study of 266 surgical cases - Feng, Fan (BMC Musculoskelet Disord, 2017)
BACKGROUND: Vertebrae, ribs, and spinal cord are anatomically adjacent structures, and their close relationships are clinically important for planning better corrective surgical approach. The objective is to identify the radiographic characteristics in surgical patients with congenital scoliosis (CS) and coexisting split cord malformation (SCM). METHODS: A total of 266 patients with CS and SCM underwent surgical treatment at our hospital between May 2000 and December 2015 was retrospectively identified. The demographic distribution and radiographic data were collected to investigate the characteristics of spine curve, vertebral, rib, and intraspinal anomalies. According to Pang’s classification, all patients were divided into two groups: type I group is defined as two hemicords, each within a separate dural tube separated by a bony or cartilaginous medial spur, while type II group is defined as two hemicords within a single dural tube separated by a nonrigid fibrous septum. RESULTS: There were 104 patients (39.1%) in Type I group and 162 patients (60.9%) in Type II group. SCM was most commonly found in the lower thoracic and lumbar regions. The mean length of the septum in Type I SCM was significantly shorter than Type II SCM (2.7 vs. 5.2 segments). Patients in Type I group had a higher proportion of kyphotic deformity (22.1%). The vertebral deformities were simple in only 16.5% and multiple in 83.5% of 266 cases. Patients in Type I group presented higher prevalence of multiple (90.4%) and extensive (5.1 segments) malformation of vertebrae. In addition, hypertrophic lamina and bulbous spinous processes were more frequent in Type I group (29.7%), even developing into the “volcano-shape” deformities. Rib anomalies occurred in 62.8% of all patients and 46.1% of them were complex anomalies. The overall prevalence of other intraspinal anomalies was 42.9%. The most common coexisting intraspinal anomalies was syringomyelia (30.5%). CONCLUSION: The current study, with the largest cohort to date, demonstrated that patients with CS and coexisting SCM presented high prevalence of multiple vertebral deformities, rib and intraspinal anomalies. The length of the split segment in Type I SCM was shorter than that in Type II SCM. Compared with Type II SCM, patients with Type I SCM presented with higher incidence of kyphotic deformity, more extensive and complicated vertebral anomalies, and more complex rib anomalies.